2019
DOI: 10.3329/jasbs.v45i1.46571
|View full text |Cite
|
Sign up to set email alerts
|

Floristic Study in Lalpur Upazila of Natore District, Bangladesh: Identification, Distribution and Economic Potential

Abstract: Floristic study in Lalpur Upazila of Natore district has identified 216 species distributed in 173 genera and 72 families, of which Magnoliopsida (Dicotyledons) is represented by 188 species under 147 genera and 60 families, while Liliopsida (Monocotyledons) is constituted by 28 species under 26 genera and 12 families. In Magnoliopsida, Asteraceae is the largest family represented by 16 species, whereas in Liliopsida, Poaceae is the largest family consisting of 8 species. The genus Solanum is the largest in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In the recent past, several attempts have been made on floristic studies in different parts of the country alongside with some protected areas (Khan and Huq, 2001;Alam et al, 2006;Tutul et al, 2010;Rahman et al, 2015;Arefin et al, 2017;Haque et al, 2018;Rashid et al, 2018). Despite sporadic studies on the flora of some upazilas of the country were carried out earlier (Moniruzzaman et al, 2012;Rahman and Alam, 2013;Rahman et al, 2012Rahman et al, , 2019, the flora of Gafargaon upazila has never been explored and the potential of its existing flora has not been evaluated. Therefore, the present study aimed at exploring and identifying the angiosperm flora of Gafargaon upazila, and to focus on the medicinally important plant resources for meeting up the primary healthcare demand of the local people.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, several attempts have been made on floristic studies in different parts of the country alongside with some protected areas (Khan and Huq, 2001;Alam et al, 2006;Tutul et al, 2010;Rahman et al, 2015;Arefin et al, 2017;Haque et al, 2018;Rashid et al, 2018). Despite sporadic studies on the flora of some upazilas of the country were carried out earlier (Moniruzzaman et al, 2012;Rahman and Alam, 2013;Rahman et al, 2012Rahman et al, , 2019, the flora of Gafargaon upazila has never been explored and the potential of its existing flora has not been evaluated. Therefore, the present study aimed at exploring and identifying the angiosperm flora of Gafargaon upazila, and to focus on the medicinally important plant resources for meeting up the primary healthcare demand of the local people.…”
Section: Introductionmentioning
confidence: 99%
“…Magnoliopsida were represented by 310 species from 242 genera while Liliopsida comprising of 67 species from 49 genera. Earlier, Rahman et al (2019) documented 216 species under 72 families and Khatun et al (2022) reported 194 species under 72 families from adjacent Lalpur and Puthia Upazila respectively. Regarding the distribution of family, Magnoliopsida and Liliopsida consist of 75 and 17 family respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The northern and eastern hill physiographic unit with sedimentary rock formations includes Upazila. In Upazila, 70% of the population are indigenous peoples, and 30% are immigrants from the lowland plains (Rahman, 2007). The primary land use activity and source of income for these people is shifting cultivation.…”
Section: Discerption Of the Study Areamentioning
confidence: 99%